2012
DOI: 10.1002/eji.201242532
|View full text |Cite
|
Sign up to set email alerts
|

Recognition of fungal RNA by TLR7 has a nonredundant role in host defense against experimental candidiasis

Abstract: Despite convincing evidence for involvement of members of the Toll‐like receptor (TLR) family in fungal recognition, little is known of the functional role of individual TLRs in antifungal defenses. We found here that TLR7 was partially required for the induction of IL‐12 (IL‐12p70) by Candida albicans or Saccharomyces cerevisiae. Moreover, the IL‐12p70 response was completely abrogated in cells from 3d mice, which are unable to mob‐ilize TLRs to endosomal compartments, as well as in cells from mice lacking ei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
42
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 54 publications
(45 citation statements)
references
References 54 publications
(96 reference statements)
2
42
0
1
Order By: Relevance
“…However, when challenged with higher doses, no significant difference was observed between TLR7-deficient mice and wild-type mice. 27 Similarly, using high dose challenges, TLR9-/-mice showed no significant alteration in survival upon clinical C. albicans isolate infection. 25,27 However, increased susceptibility to systemic candidiasis and impaired fungal clearance in TLR9-/-mice were observed upon challenge with a lower dose of C. albicans.…”
Section: The Roles Of Prrs: Findings Using Prr-deficient Micementioning
confidence: 99%
See 4 more Smart Citations
“…However, when challenged with higher doses, no significant difference was observed between TLR7-deficient mice and wild-type mice. 27 Similarly, using high dose challenges, TLR9-/-mice showed no significant alteration in survival upon clinical C. albicans isolate infection. 25,27 However, increased susceptibility to systemic candidiasis and impaired fungal clearance in TLR9-/-mice were observed upon challenge with a lower dose of C. albicans.…”
Section: The Roles Of Prrs: Findings Using Prr-deficient Micementioning
confidence: 99%
“…27 Similarly, using high dose challenges, TLR9-/-mice showed no significant alteration in survival upon clinical C. albicans isolate infection. 25,27 However, increased susceptibility to systemic candidiasis and impaired fungal clearance in TLR9-/-mice were observed upon challenge with a lower dose of C. albicans. 27 Taylor PR et al 184 investigatedb-glucan recognition and control of fungal infection using Dectin1-/-mice, and revealed that cytokine release, phagocyte recruitment, phagocytosis and microbial killing are all impaired in the Dectin1-/-mice compared with wild-type mice in disseminated candidiasis model.…”
Section: The Roles Of Prrs: Findings Using Prr-deficient Micementioning
confidence: 99%
See 3 more Smart Citations